Los Los acuerdos entre criminales y administradores de justicia penal. El arrepentido o colaborador que negocian con la justicia penal - Pablo , Galaín Palermo (2016)
Nowadays there are international organisms, which formulate criminal policy to fight against different threats to national and international public security. These policies oblige countries to implement a criminal and procedural system. The fight against whatever is defined as “organized crime” justifies the creation of the “penitent” or “collaborator”. This is the person who decides to abandon organized crime and collaborate with the criminal justice administration in order to incriminate their ex-criminal group. The collaborator should give valuable information that could not be found by using other investigation methods. The collaboration leads to a plea bargain: the collaborator could get a lighter punishment or even be released, according to the discretionary power of the prosecutor. This article gives a critical analysis of this topic in a genealogical, philosophical, normative and practical framework in Uruguay